(3fJjLI GdacQ aj GdLgQ HGdPcQs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3SCdJ CcQec Gddg Yf eG GYJGOg GdSGOI GdUhajI Yf YbO Mdb GdPcQ hGdLgQ aj GdeSLO hQaY GdUhJ HGdJgdjd s
(3BNQgG (B:s
(3aj cJGH GdRgO MOKfG MSjf Hf eMeO Hf GdeSYhOj bGd gDdGA GdPjf jRYehf Cf YHOGddg cGf jfgi Yf GdPcQ eG LGdSJ YHOGddg eLdSkG EdG PcQ Gddg YR hLd Je s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B128 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B534s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1926s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(1027 (3c(B) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs